RANCANG BANGUN SISTEM IOT UNTUK PETERNAKAN IKAN HIAS KOKI DAN MOLLY - Theresia Herlina Rochadiani (Politeknik Bisnis Indonesia, 2022)
As a country rich in fish species diversity, Indonesia was ranked as the fourth largest exporter of ornamental fish in the world from 2016 to 2019. Ornamental fish is one of the potential commodities. However, crop failure due to uncontrolled water quality such as rising ph levels is a problem that needs to be solved. As a solution, this study builds a LoRaWAN-based IoT system to be able to monitor ph, tds, and pool water temperature levels of koki and molly fish pond from anywhere and anytime through a mobile application. The sensor node uses a Heltec Lora Wi-Fi 32 v2 microcontroller that supports LoRa technology and uses the DS18B20 sensor as a temperature sensor, and a DFRobot sensor to measure ph and tds. From the test results, the accuracy of each sensor is quite good with an average error of 0.35 for temperature sensors and 0.37 for ph sensors, as well as an error percentage on tds sensors of 1.5. From the results of the implementation, the ph and temperature values in the koki fish and molly fish pond are quite good as habitats, but the tds value of pond water is quite high.